Pelatihan Literasi Numerasi Transisi PAUD SD Melalui Lagu: Early Childhood Education Elementary School Transition Numeracy Literacy Training Through Songs - Simatupang, Nurhenti Dorlina; Saroinsong, Wulan Patria; Widayati, Sri; Adhe, Kartika Rinakit; Damayanti, Maryam Isnaini (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Most young children in Indonesia experience literacy difficulties related to the alphabet and numbers in reading correctly and counting. Numeracy Literacy needs to be developed from an early age. Therefore, teachers should be able to create fun activities to develop children's literacy skills that are exciting for children. One is Primary School Early Childhood Education Transition Numeracy Literacy Training Through Songs. In developing children's literacy skills, the service team also creates songs. This service activity aims to increase teachers' knowledge regarding activities that can improve early childhood numeracy literacy skills through songs. The development model in this training uses direct observation. The target of this service is 100 PAUD teachers in Banyuwangi. The evaluation results obtained a pretest score of 45% in the